Greece : Report on Observance of Standards and Codes; Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2006)
This report provides an assessment of fiscal transparency practices in Greece in relation to the requirements of the IMF Code of Good Practices on Fiscal Transparency. The assessment reveals that Greece has made progress, in recent years, in meeting the requirements of the fiscal transparency code. This has been most marked in the area of public availability of information, with increased publications and use of the Internet. At the central government level, Greek budget processes give assurances of integrity about fiscal data through independent audit and recently strengthened statistical reporting.